PENGARUH KUALITAS PELAYANAN ROOM SERVICE DAN FASILITAS HOTEL TERHADAP KEPUASAN PELANGGAN DI V HOTEL & RESIDENCE BANDUNG - Prasetiyo, Budi; Ristiawati, Monika (Transpublika Publisher, 2022)
Hospitality is an aspect of a very large field of business and includes many access fields of work. Therefore, the hotel does not only function to provide services, but also emphasizes the service aspect. Aspects of supporting hotel services and facilities are important points in creating customer satisfaction in a hotel business, for example the completeness of hotel facilities and the friendliness of room service will be of added value in the eyes of customers. This study aims to determine the effect of the quality of room service and hotel facilities on customer satisfaction at V Hotel & Residence Bandung. This study uses a descriptive research method with a quantitative approach. In this study, the variables used are Room Service Quality (X1), Hotel Facilities (X2) and Customer Satisfaction (Y). This research carried out in V Hotel & Residence Bandung, with a total of 100 respondents. Based on the results of the research above, it can be concluded that, the quality of room service (X1) and hotel facilities (X2) partially has a significant effect on customer satisfaction (Y). This indicates that the quality of room service and hotel facilities can affect customer satisfaction V Hotel & Residence Bandung.